2012
DOI: 10.1021/ja212055x
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Borane Analogues of the Benzynes and Beyond: Bonding in Variously Charged B12H10 Isomers

Abstract: The effect of removing two protons, hydrogen atoms, or hydrides from the stable icosahedral B(12)H(12)(2-) is investigated theoretically. The resulting B(12)H(10)(q) (q = 4-, 2-, 0) isomers show interesting and understandable bond distance and stability variations, as well as special deformations associated with the apex-ring configuration typical of the underlying polyhedron. The dianions are analogous to o-, m-, and p-benzyne and have the special feature of distinct singlet and triplet states not far removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Compared to the ideal C-H (1.10 Å) and C-N (1.47 Å) single bond distances, C-H bonds are elongated by B0.05 Å while C-N bonds are shortened by 0.015 Å since the C-H bonds are aptly oriented for anomeric delocalization of the N: lone pair. The pyramidalization angle 22 of nitrogen, computed as the deviation of the sum of all the The computed band structure shows a large band-gap (Fig. 3), the conduction band minimum is at G while the valence band maximum lies in between G and K special k-points.…”
mentioning
confidence: 99%
“…Compared to the ideal C-H (1.10 Å) and C-N (1.47 Å) single bond distances, C-H bonds are elongated by B0.05 Å while C-N bonds are shortened by 0.015 Å since the C-H bonds are aptly oriented for anomeric delocalization of the N: lone pair. The pyramidalization angle 22 of nitrogen, computed as the deviation of the sum of all the The computed band structure shows a large band-gap (Fig. 3), the conduction band minimum is at G while the valence band maximum lies in between G and K special k-points.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27] We carried out MP2/6-31G* calculations on the fifteen systems [B n H n ] 2-, [1-CB n-1 H n ] -and 1,n-C 2 B n-2 H n (n = 5, 6, 7, 10, and 12) with the Gaussian09 computational package. [28] Our bond orders/indices were calculated by the Wiberg Bond Index method and the atomic and group charges by Natural Population Analysis (NPA) using the NBO 3.1 program within Gaussian09.…”
Section: The Calculational Methodsmentioning
confidence: 99%
“…65,66 Theoretical studies into B 12 H 10 q (q = 0, À2 or À4) were performed which indicated that [o-B 12 H 10 ] 2À has a singlet ground state with a short B naked -B naked distance making it an o-carboryne analogue. 67 A method to C-alkylate [1-H-CB 11 Cl 11 ] À using KOtBu and RI was reported, 68 whilst [1-H-CB 11 Cl 11 ] À partnered with the tBu cation enabled hyperconjugation and anion-cation hydrogen bonding to be probed in the solid state. 69 Cluster opening reactions have been reported on addition of a NHC to o-carborane and on addition of nucleophiles (e.g., HOR and HNR 2 ) to the 13-vertex carborane, m-1,2-(CH 2 ) 3 -1,2-C 2 B 11 H 11 .…”
Section: Metal Boryl Borylene and Related Systemsmentioning
confidence: 99%